Learned Optimism as a Mediator Between Perceived Social Support and Resilience Among Undergraduate Thesis-Writing Students - Suganda, Fildza Nurfajrina; Rubiyanti, Yanti; Fitriana, Efi; Amriwijaya, Julian (Indonesian Psychological Research, 2026)
Undergraduate thesis writing is a crucial stage in higher education that is often accompanied by psychological stress. While perceived social support and learned optimism have each been associated with resilience, few studies have specifically examined learned optimism as a mediator in the association between perceived social support and resilience among undergraduate thesis-writing students. This study aimed to investigate the role of learned optimism as a mediator in this association. This study employed a cross-sectional correlational design and involved 97 undergraduate thesis-writing students recruited through convenience sampling. The instruments used were the Multidimensional Scale of Perceived Social Support, a learned optimism scale based on Seligman’s conceptualization, and the Connor-Davidson Resilience Scale. Analyses were conducted using PROCESS with 5,000 bootstrap samples and a 95% confidence interval. The results indicated that learned optimism partially mediated the relationship between perceived social support and resilience. These findings highlight the relevance of both interpersonal and cognitive resources in understanding resilience among undergraduate thesis-writing students.